Strategi Pedagang Kaki Lima Dalam Peningkatan Perokonomian di Desa Sambi Sebagai Upaya menuju Kesejahteraan - ENI ENI SUSILOWATI; Hardining Estu Murdinar; Muh Misbahul Munir (Universitas Nahdlatul Ulama Blitar, 2022)
Street vendors are one way to make ends meet. The difficulty of available job opportunities for members of the public who have low education with very limited experience and skills. 1 Small businesses are an integral part of people's daily lives in Indonesia and in other parts of the world in general. Small businesses greatly support the ease of life of Indonesian consumers and have a very large influence on job creation as well as increasing the economic growth of a country. Street vendors in Sambi Market are one of the informal sectors and this trade sub-sector plays an increasingly important role in the economy, where the informal sector is able to absorb the workforce thereby reducing unemployment rates. Street vendors themselves are a type of informal sector business which is the largest trading group in society even though they consist of weak economic groups and structurally occupy the lowest place in Indonesia's economic strata, but in reality the informal sector provides more benefits and contributions to the economy of a country. . Referring to the description of the background and the various conditions associated with street vendors, the problems are as follows: 1) What are the strategies carried out by street vendors in increasing income for their welfare at the Sambi Village Market? 2) What are the obstacles faced by street vendors in increasing income for their welfare at the Sambi Village Market? then the research objectives to be achieved in this study are as follows 1) Want to know the strategies carried out by street vendors in increasing income for their welfare at the Sambi Village Market. 2) want to know what obstacles are faced by street vendors in increasing income for their welfare at the Sambi Village Market. This study uses a qualitative method. Qualitative approach. Data collection techniques using surveys, interviews and documentation. Based on the results of the research and discussion described in the previous chapter, the following conclusions can be drawn: Strategies carried out by street vendors in increasing income for their welfare at the Sambi Village Market: Maintain product quality, price, carry out promotions, choose strategic locations, provide good services. Well